Small Dams : Planning, Construction, and Maintenance - Lewis, Barry (Netherland CRC Press, 2013)
"A practial guide to determining catchment yield and the amount of water required in a dam. Also advises on working with engineers and contractors, and outlines the causes of dam failures and how to remedy problems quickly. It further covers relevant legislation, as well as environmental and ecological issues from a global perspective, with explicit reference to various countries around the world. An invaluable reference resource for anyone who owns or plans to own a dam, and a useful reference for agencies, contractors and engineers"--
"A Balkema Book."
Keywords: Reservoirs -- Design and construction; Water-supply, Agricultural; TECHNOLOGY & ENGINEERING / Civil / Dams & Reservoirs; TECHNOLOGY & ENGINEERING / Civil / Soil & Rock; TECHNOLOGY & ENGINEERING / Environmental / Water Supply